Вища електротехнічна освіта в Україні у другій половині ХХ ст. - Тверитникова, Олена Євгенівна (Київський національний університет ім. Т. Г. Шевченка, 2014)
Розглянуто структурні зміни системи підготовки фахівців електротехнічного профілю в провідних вищих технічних навчальних закладах України. Показано процес формування нових спеціальностей, кафедр, факультетів, філіалів, що сприяло розширенню мережі електротехнічної освіти. Висвітлено особливості діяльності навчальних закладів, зокрема організації навчального процесу, виробничої практики, науково-дослідної роботи.

The structural changes in the system of training of specialists in the electrical profile of the leading technical higher educational institutions of Ukraine are analyzed. The process of formation of the new specialties, departments, faculties, branches which lest to the expending of the network of electro-technical education is shown. Characteristics of the activity of educational institutions, in particular organization of the educational process, manufacturing practices and research work are done.
Higher electro-technical education of Ukraine the second half of the 20th century
Keywords: система підготовки; вищі технічні навчальні заклади; фахівці-електрики; електротехнічні факультети; кафедри; training system; technical colleges; electricians; electrical engineering faculties; departments